Antidumping Rules in Trade Negotiations: The Case of the Western Hemisphere - Germán A. de la Reza (Romanian Journal of European Affairs)
This paper studies antidumping trade negotiation in the Americas. It focuses on three important sides of the problem: the theoretical background of the antidumping effects on industry and consumers; the impact of the antidumping investigations in the inter-American trade, highlighting the concentration of costs on the small economies, and the alternatives voided to diminish the aggravation of the hemispheric asymmetries. The conclusion observes the importance of achieving a more-balanced negotiating outcome, taking into consideration both, economic and administrative disparities.